The mRNA for a proteinase inhibitor related to the HI-30 domain of inter-alpha-trypsin inhibitor also encodes alpha-1-microglobulin (protein HC). - Kaumeyer, J F (1986)
Inter-alpha-trypsin inhibitor (ITI) is a 180 kd serine proteinase inhibitor found in human serum. Treatment of 180 kd ITI with trypsin releases a 30 kd fragment (HI-30) which contains the anti-proteolytic activity of the high molecular weight form. We have isolated a cDNA clone from a human liver library which codes for HI-30, and have determined its DNA sequence. The mRNA not only codes for HI-30 but also another serum protein, alpha-1-microglobulin, which has not been previously associated with ITI or HI-30. The alpha-1-microglobulin sequence is found in the amino-terminus of the protein and is preceded by a signal sequence. HI-30 is found at the carboxy-terminus. The two protein sequences are separated by two arginine residues.